Dari Persepsi ke Penerimaan: Analisis TAM terhadap Penggunaan E-Learning di Perguruan Tinggi Makassar - M. Andika Aswa; Muhammad Husair Nawawi; Nurrahmah Agusnaya; Rahmawati; Rachmawaty Kadir (Academic Bright Collaboration, 2025)
The development of digital technology has driven significant changes in learning systems, including the adoption of e-learning in higher education. This study aims to analyze student acceptance of the use of e-learning platforms in Makassar City universities using the Technology Acceptance Model (TAM) framework. The three main constructs analyzed include Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Attitude Toward Using (ATU). This research uses quantitative approach with survey method, involving 65 students from various study programs who actively participate in online learning. The instrument used was a Google Form-based questionnaire consisting of 15 statements, analyzed using multiple linear regression through Jamovi software. The results showed that PU and PEOU had a positive and significant effect on ATU, with a coefficient of determination (R²) of 0.702. This means that 70.2% of the variation in student attitudes towards e-learning can be explained by these two variables. This finding confirms that perceived usefulness and ease of use are key factors in shaping positive attitudes towards learning technology adoption. This research provides an empirical contribution to the strengthening of the TAM model in the Indonesian higher education context and offers practical recommendations for the development of e-learning systems that are more effective and responsive to user needs.